Polymer Nanofiber‐Embedded Microchips for Detection, Isolation, and Molecular Analysis of Single Circulating Melanoma Cells1. Issue 12 (21st February 2013) - Hou, Shuang; Zhao, Libo; Shen, Qinglin; Yu, Juehua; Ng, Charles; Kong, Xiangju; Wu, Dongxia; Song, Min; Shi, Xiaohong; Xu, Xiaochun; OuYang, Wei‐Han; He, Rongxian; et al.
<x xml:space="preserve">Abstract</x> Confined to one cell: A method to detect and isolate single circulating melanoma cells (CMCs; see figure) has been produced by integrating a polymer‐nanofiber‐embedded nanovelcro cell‐affinity assay with a laser microdissection (LMD) technique. This method is able to separate CMCs from normal white blood cells (WBCs) and sequence individual cells for a specific mutation related to cancer progression, allowing for more personalized cancer therapy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>